Evaluating the Effectiveness of Kahoot as an Interactive Assessment Tool in Teaching Islamic Cultural History - Zulkifli Zulkifli; Muhammad Muzakki (Ar-Fachruddin: Pendidikan Agama Islam, 2025)
Research Objective – This study evaluates the effectiveness of Kahoot!, a game-based learning platform, as an interactive assessment tool in Islamic Cultural History (Sejarah Kebudayaan Islam, SKI) for fifth-grade students at MI Al-Kautsar, Sorong. Methodology – A quasi-experimental, non-randomized pretest–posttest control design was applied over four weeks (N = 53; experimental n = 27; control n = 26). Both groups received the same pretest and posttest aligned to the SKI curriculum. Descriptive statistics and paired and independent-samples t-tests were employed to examine learning gains. Findings – Both groups improved, but the experimental group achieved a larger mean gain (+20.67) than the control (+10.31), a statistically significant difference. The pattern of results suggests that Kahoot!’s real-time feedback, low-stakes competition, rapid pacing, and student-centered interface increased motivation and engagement, thereby accelerating content mastery in a text- and history-oriented subject. Effectiveness was consistent across baseline levels, indicating robustness of the observed treatment effect in typical classroom conditions. Results were educationally meaningful overall. Research Implications/Limitations – For PAI teachers, Kahoot! is suitable for formative assessment to activate prior knowledge, monitor in-lesson understanding, and consolidate learning. Effective use entails alignment with SKI objectives, a mix of recall and higher-order items, team modes, item-level analytics, and brief reflective tasks. Limitations include a single site, modest sample, short duration, and absence of qualitative data. Originality/Value – This study offers context-specific evidence from an Indonesian madrasah that technology-mediated assessment can modernize Islamic elementary education without compromising religious values, meeting the needs of digital-native learners while delivering measurable gains.